Carrageenan Matrix for Sustained Levofloxacin Delivery: Formulation Strategies and Dual Evaluation Approaches - Abdullah, Samaa; Thiab, Samar; A. Al-Masud, Alaa; Marzoog Al-Sharafa, Meshal; Ardakani, Adel (Journal of pharmaceutical innovation, 2025)
Purpose This study presents the formulation and evaluation of a sustained-release matrix tablet for levofloxacin (LFX) using carrageenan (CRG) as a natural, multifunctional excipient. Methods The complexation between LFX and CRG was optimized through saturation binding studies, demonstrating stable drug–polymer interactions mediated by hydrogen bonding and electrostatics. Comprehensive physicochemical characterization (FT-IR, DSC, PXRD, SEM) confirmed successful molecular dispersion of LFX within the CRG matrix, resulting in amorphous complex formation. Matrix tablets composed of either CRG or HPMC were assessed for swelling, erosion, in vitro drug release, and in vivo absorption. Results CRG-based systems showed enhanced swelling and erosion properties and provided sustained LFX release, contrasting with the faster release observed from HPMC matrices. In vivo pharmacokinetic studies in Wistar rats confirmed the modified release behavior, with LFX–CRG tablets exhibiting a delayed Tmax (1 h), lower Cmax (1.73 ± 0.15 µg/mL), and higher AUC₀–₂₄ (22.85 ± 1.93 µg·h/mL) compared to HPMC formulations (Cmax = 2.21 ± 0.12 µg/mL, AUC₀–₂₄ = 18.41 ± 1.26 µg·h/mL). Two-compartment pharmacokinetic modeling described the observed absorption kinetics, highlighting formulation-dependent differences in drug release and systemic exposure between CRG and HPMC matrices. These results support enhanced systemic exposure and extended release from CRG matrices. Conclusions These findings highlight the potential of CRG as an effective matrix-forming polymer in oral sustained-release systems. However, given the preclinical nature of this study, further investigations are warranted to confirm these outcomes in human subjects and evaluate formulation stability over time. Graphical Abstract